Comparative periurethral bacteriology of uncircumcised and circumcised males. Issue 4 (August 1997) - Serour, F; Samra, Z; Kushel, Z; Gorenstein, A; Dan, M
Abstract : BACKGROUND: It has been established that lack of circumcision increases the risk of urinary tract infection in infants. During the first six months, the presence of foreskin is associated with a greater quantity and a higher concentration of uropathogens in the periurethral area. Very little is known about this association in older males. OBJECTIVE: To compare the periurethral bacteriology of uncircumcised healthy males of more than one year of age. METHODS: The periurethral area of 125 uncircumcised and 46 circumcised healthy males (mean age, 26.5 and 28.3 years, respectively) was swabbed and cultured for facultative and anaerobic bacteria, genital mycoplasmas and Chlamydia trachomatis. RESULTS: Facultative Gram positive cocci predominated in both groups (62% and 80%, respectively). Pure culture of facultative Gram negative rods was more common in uncircumcised males (17% v 4% in circumcised males, p = 0.01). Streptococci, strict anaerobes and genital mycoplasmas were found almost exclusively in uncircumcised males of more than 15 years of age. No case of C trachomatis was identified. CONCLUSIONS: The higher prevalence of potential uropathogens in the subpreputial space is in accordance with a previous finding of increased risk of urinary tract infection in uncircumcised young men. Our results also support the role of the prepuce as a reservoir for sexually transmitted organisms.